THE USE OF QUANTUM TEACHING IN SPEAKING CLASS AT LAKIDENDE UNIVERSITY (A CASE STUDY) - Mclean HY (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2019)
The research was aimed at investigating the use of quantum teaching in speaking class in Lakidende University. The method of this study was a case study in order to explore and describe the phenomenon of the use of quantum teaching. The data were obtained through classroom observation, interview and questionnaire. This study was conducted at University Lakidende which was involving an English teacher and thirty five students of speaking class at the 2nd semester. Based on the result of the study, the researcher found the teacher motivated student in learning speaking by giving picture, teacher created enjoyable learning situation by asking their opinion of the learning topic then the teacher was activated students in learning speaking by making group discussion and presentation. The researcher also found the component of quantum teaching in the speaking class namely growing component, experiencing component, naming component, demonstrating component, repeating component and celebrating component. In conclusion, the use of quantum teaching in speaking class helped the students’ speaking ability at Lakidende University.   Keywords: The use of quantum teaching, teaching speaking, Components of quantum teaching